Out of the ordinary : finding hidden threats by analyzing unusual behavior - Hollywood, John S., 1973- (RAND Corp., 2004)
Presents a unique appraoch to selecting and assembling disparate pieces of information to produce a general understanding of a threat. The Atypical Signal Analysis and Processing schema identifies atypical behavior potentially related to terror actvity; puts it into context; generates and tests hypotheses; and focuses analysts' attention on the most significant findings. A supporting conceptual architecture and specific techniques for identifying and analyzing out-of-the-ordinary information are also described.